Basic principles of curriculum and instruction. - Tyler, Ralph W. (Ralph Winfred), 1902-1994.; University of Chicago. Press (Chicago: University of Chicago Press, 1969)
Proposes ways of formulating, organizing and evaluating educational objectives.
"Originally published as Syllabus for Education 360." "Published 1949."
Keywords: Education -- Curricula; Education -- Aims and objectives